2023
DOI: 10.3389/fphar.2023.1080962
|View full text |Cite
|
Sign up to set email alerts
|

Protective effects of Descurainia sophia seeds extract and its fractions on pulmonary edema by untargeted urine and serum metabolomics strategy

Abstract: Background:Descurainia sophia seeds (DS) is a herbal medicine in traditional Chinese medicine (TCM) for treating lung diseases. We aimed to evaluate the therapeutic effect of DS and five of its fractions upon pulmonary edema (PE) through metabolomics analysis (MA) of urine and serum samples of rats.Methods: A PE model was established by intrathoracic injection of carrageenan. Rats were pretreated with DS extract or its five fractions (polysaccharides (DS-Pol); oligosaccharides (DS-Oli); flavonoid glycosides (D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 73 publications
0
3
0
Order By: Relevance
“…The bioactive components of Descurainiae Semen Lepidii Semen could regulate cytokines and exert anti-inflammatory effects 313 . The main components of Descurainiae Semen Lepidii Semen are thioglycosides, isothiocyanates, flavonoids, lignans, nucleosides, organic acids, and amides 314 . Quercetin in Descurainiae Semen Lepidii Semen was metabolized by gut microbiota, such as B. fragilis , Eubacterium ramulus , and Clostridium perfringens , and it transported by MATE1 315 , 316 .…”
Section: Tcms For the Treatment Of Covid-19 Infectionsmentioning
confidence: 99%
“…The bioactive components of Descurainiae Semen Lepidii Semen could regulate cytokines and exert anti-inflammatory effects 313 . The main components of Descurainiae Semen Lepidii Semen are thioglycosides, isothiocyanates, flavonoids, lignans, nucleosides, organic acids, and amides 314 . Quercetin in Descurainiae Semen Lepidii Semen was metabolized by gut microbiota, such as B. fragilis , Eubacterium ramulus , and Clostridium perfringens , and it transported by MATE1 315 , 316 .…”
Section: Tcms For the Treatment Of Covid-19 Infectionsmentioning
confidence: 99%
“…Further studies found that the fatty oil fractions had good activity, but their anti-PH effects were not clear. 19 Therefore, the present experiment investigated whether fatty oil could exert its anti-pH effect by inhibiting PLC/IP3R/Ca 2+ signaling pathway.…”
Section: Introductionmentioning
confidence: 98%
“…18 Previous studies have shown that Descurainia sophia can reduce pulmonary inflammation, inhibit lung cancer cell proliferation, and attenuate myocardial injury and cardiac remodeling. [19][20][21] Our laboratory has previously conducted a systematic study on Descurainia sophia, and found that Descurainia sophia has good effects in treating lung diseases 22 and improving pulmonary hypertension, and can significantly inhibit the expression of PLC. 23 According to the types and polarity of Descurainia sophia, the fractions were divided into five fractions: fatty oil, oligosaccharides, flavonoid glycosides, flavonoid aglycones, and polysaccharides.…”
Section: Introductionmentioning
confidence: 99%